The procedure followed for the legal medical examination - Anane, Iuliana (Technium Social Sciences Journal, 2023)
The medical expertise activity is a necessary element and in close connection with the legal world, through legal medicine the possibility is realized through the application of justice in all situations in which it is applied, succeeding in accurately identifying a different aggressions applied to the victim. The examination must include the circumstances in which the act took place, the study of the person's body as well as the clothes worn at the time of the act, also the reasons and objectives of the examination, such as the examination of traumas, sexual assaults. A medico-legal specialist can also deduce classify the traumatic agent used, such as a blunt object, sharp bladed object, sharp point. The expert has the ability to determine the mechanism of injury based on the agent traumatic used. In the case in which the Forensic expert performs survey on victim’s sexual assault, the forensic doctor must act as urgently as possible to take the biological samples, among the obligationsa doctor has to establish the sexual maturity of the person, and to check the presence of different traumas that can be observed on the genital organ. Examination applied to the male individual being the establishment of the sexual capacity for fecundation, the inability to copulation it may be formula on the base of different factors, such as: the mental state due to fears or nervousness or due tovarious causes.